Penerapan Seven Tools dalam Identifikasi dan Perbaikan Cacat Produk pada Proses Produksi Roti D’One - Febrianti Galingging; Lisa Ardea; Muhammad Zhorvan El Parisi; Mujib Qalsyi; Syabila Adrinamira Mumtaz; Velika Anandita Humaira (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the bread production system of UMKM Roti D’One using the Input–Process–Output (IPO) approach and to identify product defects through the application of the Seven Tools of quality control. Data were obtained through interviews, field observations, and production recording. The IPO analysis shows that the production process is carried out manually and relies heavily on worker skills and household-scale equipment. Based on the checksheet, two dominant types of defects were identified—non-soft texture and uneven color—resulting in 30 defective products out of 1,400 breads produced in one week. The Pareto analysis indicates that texture defects contribute the largest portion (56.7%) of total defects. Meanwhile, the fishbone diagram reveals that the main causes originate from raw material inconsistency, equipment limitations, variations in worker skills, and manual production methods. This study suggests improvements related to raw material standards, production consistency, and worker training to reduce defects and enhance the overall quality of Roti D’One products.